On Committees of Experts - Bauke Visser; Otto H. Swank (Tinbergen Institute, 2005)
A committee makes a decision on a project on behalf of the public. Members of the committee agree on the a priori value of the project, and hold additional private information about its consequences. They are experts who care about the value of the project and about being considered well informed. Before voting on the project, members can exchange their private information simultaneously. We show that reputational concerns make the a priori unconventional decision more attractive and lead committees to show a united front. These results hold irrespective of whether information can be manipulated or not. Also, reputational concerns induce members to manipulate information and vote strategically if their preferences differ considerably from those of the member casting the decisive vote. Our last result is that the optimal voting rule balances the quality of information exchange and the alignment of interests of the decisive voter with those of the public.
Keywords: D71; D72; D82; 330; Committees; communication; reputational concerns; strategic voting; Sachverständige; Gruppenentscheidung; Reputation; Spieltheorie